Effect of acupuncture on post-stroke dysphagia: a randomized controlled trial - Bai, Lin; Cheng, Hongliang; Hu, Peijia; Wang, Qingqing; Shilin, Zhang; Shen, Zhiqiang; Xu, Fangyuan; Su, Xingxing; Zhang, Yiting (Frontiers in Neurology, 2024)
Introduction Post-stroke dysphagia (PSD) is associated with various complications that increase morbidity and mortality rates. Acupuncture has been used extensively in China to treat these complications; however, its therapeutic efficacy remains uncertain. We therefore aimed to study the clinical effects of acupuncture on PSD. Methods Patients (n = 101) were randomly divided into acupuncture (n = 50) and rehabilitation training control (n = 51) groups based on the treatment used. Both groups were treated once daily, 6 days a week, for a total of 4 weeks. Pulse oxygen saturation (SpO2) and standardized swallowing assessment (SSA) were performed before the intervention, 2 weeks into treatment, after the intervention (4 weeks post-intervention), and at a 6-month follow-up (28 weeks). The levels of hemoglobin (Hb) and albumin (ALB), and 5-hydroxytryptamine (5-HT) and dopamine (DA) were measured before the intervention, 2 weeks into treatment, and after the intervention (4 weeks), as nutrition and swallowing function indices, respectively. Results Following the intervention, significant differences were observed between the acupuncture and control groups. The acupuncture group exhibited considerably superior enhancements in SpO2 and SSA scores at 4 weeks (p < 0.001). Moreover, this group demonstrated significantly greater improvements in Hb, ALB, 5-HT, and DA values 4 weeks post-treatment (p < 0.001). However, sex-based differences were not observed (P > 0.005). Conclusion Acupuncture treatment can improve the swallowing function and nutritional status of patients with PSD, and increase the levels of 5-HT and DA. These findings strongly support the efficacy of acupuncture as a therapeutic intervention in patients with PSD. Clinicaltrial registration: identifier, ChiCTR2100052201. (https://www.chictr.org.cn/).